Murdoch mysteries. Season 08 [videorecording (DVD)] - Bisson, Yannick, 1969-; Joy, Hélène; Reilly, Georgina; Jennings, Maureen (ITV Studios, 2015)
In Season 8 of this delightful detective show, joy and heartbreak await Detective William Murdoch and his friends in turn-of-the-century Toronto. After his brutal beating by the dockyard gang, Inspector Brackenreid's future remains uncertain. Constable Crabtree faces life-altering changes, including a new romance, while Dr. Emily Grace and Dr. Julia Ogden join the women's suffrage movement. And in the show's 100th episode, wedding bells ring as Murdoch and Julia finally walk down the aisle.